Bureaucratic Reform and Political Elite Behavior Change: The Impact of Merit System on Political Patronage in Regional Government - Abd Haris; Hermansyah Hermansyah; Kiki Rasmala Sani; Suardi Mukhlis (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
This study examines the impact of bureaucratic reform through merit system implementation on political elite behavior and patronage politics practices in regional government. Using a mixed-method approach combining quantitative analysis of 150 regional governments and qualitative case studies in five provinces during 2019-2024, this research investigates how civil service recruitment reforms influence transactional political practices. The study employs New Public Management theory, political patronage theory, and institutional change theory to analyze the transformation of elite behavior. Results indicate that merit system implementation significantly reduces political patronage practices (β = -0.627, p < 0.001), with stronger effects in regions with higher institutional capacity and civil society oversight. However, political elites adapt by shifting patronage mechanisms from recruitment to procurement and project allocation. The study reveals that successful bureaucratic reform requires simultaneous strengthening of transparency mechanisms, political accountability, and civil society participation. These findings contribute to understanding the complex relationship between administrative reform and political behavior change in decentralized governance systems.